Assessment Methods and Interventions to Develop Computational Thinking - A Literature Review - Vinu Varghese, V.V.; Renumol, V.G. (2021 International Conference on Innovative Trends in Information Technology (ICITIIT), 2021)
Computational Thinking (CT) allows us to solve complex problems by expressing it in a way that computers, humans, or both, can understand. CT is closely related to problem solving and critical thinking, which are actively used in STEM education. Research on CT has gained steady momentum recently, and many of the institutions around the world have adopted CT into their curriculum. This paper presents a literature review conducted to identify the interventions used to develop CT skills and the methods used to assess CT skills. The review explored various publications on CT and identified that curriculum-based interventions and workshops are the primary interventions used for introducing CT in the educational sector. During the analysis, we have also identified a handful of assessment tools used for measuring CT skills, but they are not standardized assessment tools. Hence, we plan to analyze the existing assessment methods and propose a new sophisticated tool for evaluating CT skills as our future work.